The use of adverbs in Ngor-Okpala dialect of Igbo - Nwachukwu, Emmanuel Lucas (Yayasan Mitra Persada Nusantara, 2025)
Adverbs play a crucial role in language by providing additional information about various elements of a sentence such as verbs, adjectives, other adverbs, prepositional phrases, subordinate clauses, and even complete sentences. Very little attention has been given to usage-based approach to parts of speech, particularly the use of adverbs in different dialects, this study investigates the use of adverbs in Ngor-okpala dialect of Igbo. Adverbs in Igbo language is known as Nkwuwa or Enyemaka Ngwaa, Adverbs in the dialect are used to answer questions such as